Biophysical Control of Bile Duct Epithelial Morphogenesis in Natural and Synthetic Scaffolds - Funfak, Anette; Bouzhir, Latifa; Gontran, Emilie; Minier, Nicolas; Dupuis-Williams, Pascale; Gobaa, Samy (Frontiers in Bioengineering and Biotechnology, 2019)
The integration of bile duct epithelial cells (cholangiocytes) in artificial liver culture systems is important in order to generate more physiologically relevant liver models. Understanding the role of the cellular microenvironment on differentiation, physiology and organogenesis of cholangiocytes into functional biliary tubes is essential for the development of new liver therapies, notably in the field of cholangiophaties. In this study, we investigated the role of natural or synthetic scaffolds on cholangiocytes cyst growth, lumen formation and polarization. We demonstrated that cholangiocyte cyst formation efficiency can be similar between natural and synthetic matrices provided that the mechanical properties of the hydrogels are matched. When using synthetic matrices, we also tried to understand the impact of elasticity, MMP-mediated degradation and integrin ligand density on cyst morphogenesis. We demonstrated that hydrogel stiffness regulates cyst formation. We found that controlling integrin ligand density was key in the establishment of large polarized cysts of cholangiocytes. The mechanism of lumen formation was found to rely on cell self-organization and proliferation. The formed cholangiocyte organoids showed a good MDR1 (multi drug resistance protein) transport activity. Our study highlights the advantages of fully synthetic scaffold as a tool to develop bile duct models.